2005
DOI: 10.1021/bi0509393
|View full text |Cite
|
Sign up to set email alerts
|

Sites and Mechanisms of Aconitase Inactivation by Peroxynitrite:  Modulation by Citrate and Glutathione

Abstract: Aconitases are iron-sulfur cluster-containing proteins present both in mitochondria and cytosol of cells; the cubane iron-sulfur (Fe-S) cluster in the active site is essential for catalytic activity, but it also renders aconitase highly vulnerable to reactive oxygen and nitrogen species. This study examined the sites and mechanisms of aconitase inactivation by peroxynitrite (ONOO-), a strong oxidant and nitrating agent readily formed from superoxide anion and nitric oxide generated by mitochondria. ONOO- inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 48 publications
2
107
0
1
Order By: Relevance
“…Although sulfenic acid formation is readily reversible by GSH, it is unstable and can undergo further oxidation to sulfinic and sulfonic acids, which represent irreversible modifications. Recently, it has been shown that treatment of the mitochondrial protein aconitase with ONOO Ϫ results in sulfonic acid formation on cysteines residues and an inhibition of activity (9). ROS or RNS can also cause vicinal thiols or thiols from different proteins to undergo intra-or intermolecular disulfide bridge formation, respectively.…”
Section: Protein Thiol Modifications By Ros and Rns Ros And Rns Can mentioning
confidence: 99%
“…Although sulfenic acid formation is readily reversible by GSH, it is unstable and can undergo further oxidation to sulfinic and sulfonic acids, which represent irreversible modifications. Recently, it has been shown that treatment of the mitochondrial protein aconitase with ONOO Ϫ results in sulfonic acid formation on cysteines residues and an inhibition of activity (9). ROS or RNS can also cause vicinal thiols or thiols from different proteins to undergo intra-or intermolecular disulfide bridge formation, respectively.…”
Section: Protein Thiol Modifications By Ros and Rns Ros And Rns Can mentioning
confidence: 99%
“…Gene expression of pro-inflammatory cytokines is also inhibited by electrophiles. For example, electrophilic alkylation of the pro-inflammatory transcription factor, nuclear factor-B (NF-B) modifies critical thiols in the p65 and p50 subunits, in turn suppressing DNA binding and NF-〉 target gene activation (12)(13)(14)(15)(16). Fatty acid-derived electrophiles also serve as ligands for receptors activated by the modulation of a critical Cys; for * This work was supported in part by National Institutes of Health Grants example, 15-deoxy-⌬ 12,14 -PGJ 2 (15dPGJ 2 ) binds to peroxisome proliferator-activated receptor-␥ (PPAR␥), increasing transcription of PPAR response element-regulated genes (17)(18)(19).…”
mentioning
confidence: 99%
“…Aside from the biological consequences that we will discuss below, inactivation of either form of aconitase can help to trace the origin, mitochondrial or cytoplasmic, of O 2 •− (Han et al, 2005) in any given situation (although escape of part of mitochondrially generated O 2 •− to the cytoplasm can blur the situation). For example, Kumar et al (2006) have observed that intermittent hypoxia caused a preferential decrease in the activity of mitochondrial aconitase suggesting that the main locus of O 2 •− generation in these situations is mitochondria.…”
Section: General Reactivity Of Superoxide Anionmentioning
confidence: 99%
“…Obviously, inactivation of mitochondrial aconitase leads to a decrease in the Krebs activity with the subsequent impairment of energy production. However, the extension of damage depends on several factors (Han et al, 2005): (a) activity of mitochondrial SOD, as for example null mice for mitochondrial SOD exhibited marked reduction (in comparison to controls) in the activity of aconitase as well in the iron-sulfur containing respiratory complexes I and II-III; (b) abundance of iron-sulfur enzymes (varies from tissue to tissue); and (c) the concentration of citrate which is protective and the presence of NO • . NO • can react with O 2 •− to form peroxynitrite (at a nearly diffusion controlled rate; ONOO − ; see below) which is very strong oxidant and nitrating agent capable of attacking the iron-sulfur clusters, nitrating tyrosine residues and oxidizing cysteine residues, and indeed producing loss of aconitase activity and other iron-sulfur clustercontaining enzymes (Han et al, 2005).…”
Section: General Reactivity Of Superoxide Anionmentioning
confidence: 99%
See 1 more Smart Citation